International Unionism: The Papermakers in Eastern Canada, 1930-1945 - Williams, C. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
This paper examines the case of the United Papermakers and Paperworkers in the province of Quebec and its conflict with the provincially centered Federation nationale des travailleurs de la pulpe et du papier Inc.